The Role State Sukuk Instruments to Support Halal Industry - Trimulato, Trimulato; Syarifuddin, Syarifuddin (Benefit: Journal of Bussiness, Economics, and Finance, 2023)
The Purpose study describe development state Sukuk, halal industry, and role state Sukuk support halal industry. Method used research is qualitative type literature study. Source data used study is secondary, from data has been previously presented certain institutions. Data from Financial Services Authority, Directorate General Financing and Risk Management Ministry Finance and other. Data collection techniques are literature relevant theme. Data analysis technique used descriptive qualitative, which describes development State Sukuk, development Halal Industry, and role State Sukuk support halal industry. Results showed development state Sukuk instrument 2019 to 2020. Sukuk experienced largest growth PBS type Sukuk with private settlement scheme 214.39%, retail Sukuk 72.93%, PBS auction Sukuk 39.59%. Savings Sukuk decreased -35.76 percent, and SPN-S Sukuk decreased -30.01 percent. State Sukuk can support halal industry, including in terms direct capital, support establishment infrastructure directed towards supporting halal industry, for example, support in terms product marketing strategies and other activities.